KINETIC EVALUATION OF ETHANOL-TOLERANT THERMOPHILE Geobacillus thermoglucosidasius M10EXG FOR ETHANOL PRODUCTION - Eny Ida Riyanti; Peter L. Rogers (Indonesian Agency for Agricultural Research and Development, 2009)
Thermophiles are challenging to be studied for ethanol production using agricultural waste containing lignocellulosic materials rich in hexose and pentose. These bacteria have many advantages such as utilizing a wide range of substrates, including pentose (C5) and hexose (C6). In ethanol production, it is important to use ethanol tolerant strain capable in converting lignocellulosic hydrolysate. This study was aimed to investigate the growth profile of ethanol-tolerant thermophile Geobacillus thermoglucosidasius M10EXG using a defined growth medium consisted of single carbon glucose (TGTV), xylose (TXTV), and a mixture of glucose and xylose (TGXTV), together with the effect of yeast extract additionto the media. The experiments were conducted at the School of Biotechnology and Biomolecular Sciences of The University of New South Wales, Australia on a shake flask fermentation at 60°C in duplicate experiment. Cultures were sampled every two hours and analised for their kinetic parameters including the maximum specific growth rate (µmax), biomass yield (Yx/s), ethanol and by-product yields (acetate and L-lactate) (Yp/s), and the doubling time (Td). Results showed that this strain was capable of growing on minimal medium containing glucose or xylose as a single carbon source. This strain utilized glucose and xylose simultaneously (co-fermentation), although there was glucose repression of xylose at relatively low glucose concentration (0.5% w/v), particularly when yeast extract (0.2% w/v) was added to the medium. The highest biomass yield was obtained at 0.5 g l-1 on glucose medium; the yield increased when yeast extract was added (at 0.59 g l-1). The highest specific growth rate of 0.25 was obtained in the phase I growth when the strain was grown on a mixture of glucose and xylose (0.5% : 0.5% w/v) medium. Diauxic growth was shown on the mixture of glucose, xylose, and yeast extract. The strain produced low level of ethanol (0.1 g l-1), as well as low level (0.2 g l-1) of by-products (L-lactate and acetate) after 15 hours. The results suggests its potential application for fermenting lignocellulosic agricultural wastes for ethanol production.